"Resumption of Sexuality and Health Education in Postpartum Period: From Jordanian Health Care Professionals' Perspectives". Issue 7 (2nd October 2020) - Alnuaimi, Karimeh; Almalik, Mona; Mrayan, Lina; Mohammad, Khitam; Ali, Reem; Alshraifeen, Ali
Abstract: Objective: to explore Jordanian health care professionals' perspectives about sexual education after giving birth. Methods: a descriptive qualitative approach was used to address the study aim. A purposive sampling method was used to recruit seven midwives, 13 nurses and two obstetricians from three Primary Health Centres. The inclusion criteria were: midwives, nurses or obstetricians with at least two years' experience and currently working at a maternity health centre. Focus group discussions were used to collect data. A manual Thematic Content Analysis Tool was used to analyse the data. Results: five major themes emerged. Silence; resumption of sexuality after giving birth/area of conflict; men's authority in resumption of sexuality; the importance of sexual education (what, when and whom) and suggestions for sexual education approaches. Conclusions: Healthcare professionals were hesitant to open sexuality topic with the women during antenatal and postnatal visits due to cultural limitations and lack of knowledge. Therefore, in a time of global migration, the healthcare professionals have the need to understand cultural differences in attitude towards health care issues involving sexuality.